Molecular Docking, Dynamics Simulations, ADMET, and DFT Calculations: Combined In Silico Approach to Screen Natural Inhibitors of 3CL and PL Proteases of SARS-CoV-2 - Sugumar Mohanasundaram; Porkodi Karthikeyan; Venkatesan Sampath; M. Anbazhagan; Sundramurthy Venkatesa Prabhu; Jamal M. Khaled; Muthu Thiruvengadam (Cellular Microbiology)
Considering natural compounds for the antiviral effect is another opportunity for exploring novel drug candidates for severe acute respiratory syndrome coronavirus 2. The selected natural compounds were interacted using a molecular docking approach. The 3D structures of the main protease and papain-like protease were used for the virtual screening to detect the potent inhibitor against SARS-CoV-2. The top-scored compounds were further analyzed for absorption, digestion, metabolism, excretion, and toxicity properties and density functional theory analysis. Our results indicated that glycyrrhizin exhibited better docking scores of -9.5 kcal/mol with main protease and -9.7 kcal/mol with papain-like protease. Next to glycyrrhizin, rutin showed a better docking score of -9.1 kcal/mol and -9.2 kcal/mol with 3-chymotrypsin-like and papain-like proteases. Violaxanthin and naringin occupied the subsequent position in the docking score table with 3CL and PL proteases, respectively. In addition, the crucial properties like drug likeliness and pharmacokinetics of the compounds were determined. There is no significant toxicity identified.